Impact of spot size on plan quality of spot scanning proton radiosurgery for peripheral brain lesions. Issue 12 (17th November 2014) - Wang, Dongxu; Dirksen, Blake; Hyer, Daniel E.; Buatti, John M.; Sheybani, Arshin; Dinges, Eric; Felderman, Nicole; TenNapel, Mindi; Bayouth, John E.; Flynn, Ryan T.
Abstract : Purpose: To determine the plan quality of proton spot scanning (SS) radiosurgery as a function of spot size (in‐air sigma) in comparison to x‐ray radiosurgery for treating peripheral brain lesions. Methods: Single‐field optimized (SFO) proton SS plans with sigma ranging from 1 to 8 mm, cone‐based x‐ray radiosurgery (Cone), and x‐ray volumetric modulated arc therapy (VMAT) plans were generated for 11 patients. Plans were evaluated using secondary cancer risk and brain necrosis normal tissue complication probability (NTCP). Results: For all patients, secondary cancer is a negligible risk compared to brain necrosis NTCP. Secondary cancer risk was lower in proton SS plans than in photon plans regardless of spot size ( p = 0.001). Brain necrosis NTCP increased monotonically from an average of 2.34/100 (range 0.42/100–4.49/100) to 6.05/100 (range 1.38/100–11.6/100) as sigma increased from 1 to 8 mm, compared to the average of 6.01/100 (range 0.82/100–11.5/100) for Cone and 5.22/100 (range 1.37/100–8.00/100) for VMAT. An in‐air sigma less than 4.3 mm was required for proton SS plans to reduce NTCP over photon techniques for the cohort of patients studied with statistical significance ( p = 0.0186). Proton SS plans with in‐air sigma larger than 7.1 mm had significantly greater brain necrosis NTCP than photon techniques ( p = 0.0322). Conclusions: For treating peripheral brain lesions—where proton therapy would be expected to have the greatest depth‐dose advantage over photon therapy—the lateral penumbra strongly impacts the SS plan quality relative to photon techniques: proton beamlet sigma at patient surface must be small (<7.1 mm for three‐beam single‐field optimized SS plans) in order to achieve comparable or smaller brain necrosis NTCP relative to photon radiosurgery techniques. Achieving such small in‐air sigma values at low energy (<70 MeV) is a major technological challenge in commercially available proton therapy systems.